Dipolarization Fronts With Associated Energized Electrons in Saturn's Magnetotail. Issue 4 (19th April 2018) - Smith, A. W.; Jackman, C. M.; Thomsen, M. F.; Sergis, N.; Mitchell, D. G.; Roussos, E.
Abstract: We present a statistical study of dipolarization fronts within Saturn's magnetotail. Automated methods were used to identify 28 significant southward rotations of the field coupled with enhancements in the electron energy. The observed dipolarizations cover the majority of the magnetotail, though possess a strong dawn‐dusk asymmetry (79% occur postmidnight). Almost half (43%) of dipolarizations occur within 3 hr of another event, though these chains are solely observed postmidnight. Most pitch angle distributions of the heated electron populations show increased relative fluxes parallel or perpendicular to the field, likely due to nonlocal heating effects. The electron temperature and density following the passage of a front are anticorrelated; the temperature increases are accompanied by a decrease in their density. The temperature increases by factors of 4–12, while the density drops by factors of 3–10. Premidnight events consistently show the smallest relative heating and density depletion, suggesting they are observed closer to their generation. In contrast, the location of the postmidnight x‐line is inferred to be more variable, with a large variety of heating factors observed. Forty percent of the events show a strong reduction in water ( W + ) group fraction, likely related to either the preferential loss of equatorial heavy ions in departing plasmoids or the closure of open field. Two of these events show significant compositional changes suggesting the addition of plasma of external origin; we suggest that these events involved the closure of open field. Key Points: Automated methods used to identify coincident southward field rotations and electron energizations Dipolarizing material shows a systematic increase in electron temperature and reduction in density Electron heating and density changes exhibit a larger range of variation postmidnight